Sex-specific trajectories of measures of cardiovascular health during childhood and adolescence: A prospective cohort study. (November 2018) - O'Keeffe, Linda M.; Simpkin, Andrew J.; Tilling, Kate; Anderson, Emma L.; Hughes, Alun D.; Lawlor, Debbie A.; Fraser, Abigail; Howe, Laura D.
Abstract: Background and aims: Sex differences in measures of cardiovascular health in adults are well documented. However, the sex-specific aetiology of cardiovascular health across childhood and adolescence is poorly understood. Methods: We examined sex differences in trajectories of 11 measures of cardiovascular health from birth to 18 years, in a contemporary birth cohort study in England (N participants per outcomes: 662-13, 985, N repeated measures per outcome: 1, 831-112, 768). Outcomes were measured over varying time spans from birth or mid-childhood to age 18 and with different numbers of repeated measures per outcome. Analyses were performed using fractional polynomial and linear spline multilevel models. Results: Females had higher mean BMI, height-adjusted fat mass, pulse rate, insulin, triglycerides, and non-high-density lipoprotein cholesterol (HDL-c) and lower mean height-adjusted lean mass from birth or from mid-childhood to age 18. For example, mean non-HDL-c was 0.07 mmol/l (95% confidence interval (CI), 0.04, 0.10) higher in females compared with males at birth. By age 18, this difference persisted and widened to 0.19 mmol/l (95% CI, 0.16, 0.23) higher non-HDL-c in females compared with males. Females had lower levels of glucose from mid-childhood and developed lower systolic blood pressure and higher HDL-c from mid-adolescence onward. For example, females had 0.08 mmol/l (95% CI, 0.05, 0.10) lower mean glucose compared with males at age seven which widened to a difference of 0.22 mmol/l (95% CI, 0.25, 0.19) at age 18. Conclusions: Sex differences in measures of cardiovascular health are apparent from birth or mid-childhood and change during early life. These differences may have implications for sex-specific disease risk in future adult populations. Highlights: Sex differences in measures of cardiovascular health are well established in adulthood. Few studies have examined sex-specific change in cardiovascular risk in childhood. Our findings show that sex differences in cardiovascular health begin at birth. These sex differences change further throughout childhood and adolescence. Early life factors may play a role in sex differences in cardiometabolic disease.